Revisiting the importance of residual source material (restite) in granite petrogenesis: The Cardigan Pluton, New Hampshire - Dorais, M.J.; Spencer, Christopher (Elsevier BV, 2014)
The Cardigan Pluton of New Hampshire exhibits a positive correlation between peraluminosity with maficity, with as much as 8% normative corundum in rocks with 53 wt.% SiO2. No mafic magmas of these compositions exist; the whole-rock compositions reflect high concentrations of garnet. The mafic rocks have higher CaO concentrations than garnet and require high concentrations of plagioclase as well. The presence of melt depleted, restitic garnetites in the pluton that are in isotopic equilibrium with the host rocks provides evidence for the textures and compositions of restitic plagioclase and peritectic garnet that can be compared to plagioclase and garnet in the host rocks. Some restitic grains of plagioclase in the garnetites contain needles of rutile and ilmenite. Plagioclase crystals with these same inclusions are also present in the host rocks. Inclusion-bearing plagioclase in both settings has identical Sr, Ba, Eu, Pb, and Ga concentrations, indicating that these crystals in the host rock are also restite. Most host rock plagioclase crystals that lack inclusions have higher Ba concentrations resulting from the fractionation of Ba which was an incompatible element until K-feldspar crystallized; these are phenocrysts. Peritectic garnet is inclusion-rich and has flat chondrite-normalized HREE patterns. The HREE elements incorporated into peritectic garnet were continuously supplied by zircon during the melting process. Once the melt separated from the source, fractionation of zircon and garnet depleted the melt in the HREE and phenocrystic garnet shows a progressive depletion in HREE from cores to rims. Peritectic garnet entrained in the host rocks show the same textural and chemical characteristics as garnet in the garnetites, but is mantled by inclusion-poor, HREE depleted, phenocrystic garnet. The Cardigan Pluton thus contains both peritectic garnet and restitic plagioclase, the retention of which in variable amounts can account for the range of whole-rock compositions of the pluton. If retention of relatively high density peritectic garnet occurs in other granitic plutons, then retention of lower density restitic phases such as plagioclase should occur as well, lending legitimacy to the peritectic/restitic phase entrainment/unmixing model in peraluminous plutons.